2020
DOI: 10.1097/scs.0000000000006929
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical Orthopedic Intervention Prior to Cleft Lip and Palate Repair: Nasoalveolar Molding Versus Passive Molding Appliance Therapy

Abstract: Background: Nasoalveolar molding (NAM) is a widely used presurgical orthopedic device, despite disputes over its effectiveness. This study compares the outcomes after cleft lip and nose repair in patients who received NAM versus those who underwent passive alveolar molding with lip taping. Methods: A retrospective review of patients with complete unilateral cleft lip and palate who received either NAM (n = 16) or passive molding (n = 10) treatments was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 29 publications
0
25
0
2
Order By: Relevance
“…In contrast, nasoalveolar molding has been criticized for the high treatment burden, visits, and thus healthcare costs [ 30 ]. It was shown that these costs could be reduced with passive presurgical treatment [ 31 ]. This could also counteract early cleft lip surgery in the first weeks of life, which has been propagated to reduce the burden of health care costs [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, nasoalveolar molding has been criticized for the high treatment burden, visits, and thus healthcare costs [ 30 ]. It was shown that these costs could be reduced with passive presurgical treatment [ 31 ]. This could also counteract early cleft lip surgery in the first weeks of life, which has been propagated to reduce the burden of health care costs [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lip taping is offered by 53% of survey respondents in our study, and maybe the preferred modality for certain patients due to the aforementioned criteria. While the results of lip taping may be suboptimal compared with NAM, the alveolar cleft gap is still reduced with its employment 41. Compared with no PSIO therapy, lip taping efficiently changes the maxillary arch dimension using passive lip pressure, thus facilitating a lip repair procedure with reduced tension 42.…”
Section: Discussionmentioning
confidence: 99%
“…While the results of lip taping may be suboptimal compared with NAM, the alveolar cleft gap is still reduced with its employment. 41 Compared with no PSIO therapy, lip taping efficiently changes the maxillary arch dimension using passive lip pressure, thus facilitating a lip repair procedure with reduced tension. 42 If the surgeon intends to perform a gingivoperiosteoplasty and requires that segments abut, the modality of choice would still be NAM.…”
Section: Lip Tapingmentioning
confidence: 99%
“…La terapia prequirúrgica debe iniciar idealmente al momento del nacimiento [3][4][5]9 . En países de recursos limitados, la atención temprana y oportuna se dificulta debido a que los centros de referencia para la atención multidisciplinaria de estos pacientes son escasos.…”
Section: Materiales Y Métodosunclassified
“…En la última década distintas técnicas han sido utilizadas por varios centros multidisciplinarios alrededor del mundo con este fin. 3,4 El propósito común de la técnica de Ortopedia Funcional Maxilar (OFM)-Moldeado Nasal (MN), descrita por Pannaci 5 y el Retractor nasal (RN)-Taping modificación Hinostroza 6 en pacientes con LPHU es disminuir la amplitud de la brecha alveolar y palatina y moldear el cartílago alar del lado afectado para reducir la necesidad de disecciones mayores con la consecuente tensión en el labio superior ya reparado. La diferencia entra ambas técnicas es la placa OFM, que no se usa en la técnica RN-Taping.…”
Section: Introductionunclassified